1994
DOI: 10.1039/an9941900677
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of metal ion interactions with wool keratin using chemometrics

Abstract: Uptakes of chromium(m), copper(Ir), iron(Ii), nickel(I1) and zinc(n) by wool were determined by inductively coupled plasma atomic emission and flame atomic absorption spectrometry. The order of uptakes at 100 "C for these metal ions was found to be Cu" > > Zn" > Crm > Fen > Ni".Further, the metal ion-treated wool samples were submitted to Fourier transform infrared spectrometric analysis, which was facilitated by chemometric methods (principal components analysis, soft independent modelling of class analogies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…As a protein fibre, wool has polar and ionisable groups on the side chain of constituent amino acid residues that can bind both inorganic and organic charged molecules . A wide range of metal ions can be bound to wool, such as aluminium, mercury, copper, iron, nickel, zinc, cobalt, chromium, silver and gold .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a protein fibre, wool has polar and ionisable groups on the side chain of constituent amino acid residues that can bind both inorganic and organic charged molecules . A wide range of metal ions can be bound to wool, such as aluminium, mercury, copper, iron, nickel, zinc, cobalt, chromium, silver and gold .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the formation of metal–wool complexes primarily takes place at free carboxyl groups in the wool, and relatively large uptakes of metal ions do not necessarily lead to significant structural changes in wool keratin . Smith and co‐workers suggested that metal ions could bind to a number of functional groups in proteins, such as carboxylic acid groups and sulphur‐containing groups.…”
Section: Resultsmentioning
confidence: 99%
“…Along with the reduced intensity of the peak at 2929 cm -1 , it can be inferred that PEI was successfully immobilised on wool [9]. In the FTIR spectra of copper wool, there is a reduction in the intensity of peaks at 1523 cm -1 , 1639 cm -1 and 1234 cm -1 indicating the interaction of the metal with the amide I (N-H stretching bond), amide II (C-N stretching bond) and amide III (N-H bending bond) indicating the formation of copper-keratin complex on wool [26]. The immobilisation of copper on wool was further confirmed by UV spectroscopy.…”
Section: Spectroscopic Analysis Of Woolmentioning
confidence: 94%
“…Proteinaceous substances in the test walls of the agglutinated foraminifera would cause absorptions to occur in these spectral regions. l n all spectra, carbonyl ( G O , stretch) and N-H (bending) vibrations are identified at around 1650cm-' relating to the amide 1 unit, the main peptide link, of a protein (Kokot et a/., 1994). Within the amide 1 region, small absorptions can identify features of the secondary structure of the protein i.e.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 98%
“…Absorptions in the regions 1500-1600 and 2800-3000cm-' arise from the vibration of organic materials in the test wall. The broad absorption between 3000 and 3800 cm-l is produced from fundamental OH-stretching vibrations in inorganic and organic materials (Graetsch et al, 1985), and N-H bond stretches from organic materials (Kokot et al, 1994).…”
Section: Raman Spectroscopymentioning
confidence: 99%